ANALYSIS OF A PEAK GROUND ACCELERATION VALUE AND EARTHQUAKE INTENSITY USING DONOVAN METHOD IN BANTEN PROVINCE - Ariani, Elsi (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
Analysis of a peak ground acceleration value and earthquake intensity in Banten Province has been carried out using historical earthquake data from 2008 to 2018. This research aims to describe a prone area of the earthquake. The specification of data was a magnitude > 5 SR and the depth 0-70 km. The Donovan method was used to analyze peak ground acceleration value and the earthquake’s intensity. According to the data obtained, 31 earthquake points with a maximum earthquake strength occurred on October 16, 2019, with a depth of 10 km and a magnitude of 6.48 SR. This earthquake was located in Ujung Kulon with coordinates -6.81 LS and 105.113 BT. Based on data analysis result was obtained a peak ground acceleration value and the intensity of earthquake maximum in The Pandeglang Regency with a peak ground acceleration value was 211.56 cm/s2, and intensity of scale VIII and a large risk level of three. While a peak ground acceleration minimum is located in the South Tangerang City was 62.82 cm/s2 with a scale of intensity VII and a moderate risk level.